Oxytocin Increases Phasic and Tonic GABAergic Transmission in CA1 Region of Mouse Hippocampus - Maniezzi, Claudia; Talpo, Francesca; Spaiardi, Paolo; Toselli, Mauro; Biella, Gerardo (Frontiers in Cellular Neuroscience, 2019)
Oxytocin is a neuropeptide that plays important peripheral and central neuromodulatory functions. Our data show that, following activation of oxytocin receptors (OtR) with the selective agonist TGOT, a significant increase in frequency and amplitude of spontaneous inhibitory postsynaptic currents (sIPSC) occurred in hippocampal CA1 pyramidal neurons (PYR) in mice. TGOT affected also sIPSC deactivation kinetics, suggesting the involvement of perisynaptic GABAA receptors (GABAAR) as well. By contrast, TGOT did not cause significant changes in frequency, amplitude or deactivation kinetics of miniature IPSC, suggesting that the effects elicited by the agonist are strictly dependent on the firing activity of presynaptic neurons. Moreover, TGOT was able to modulate tonic GABAergic current mediated by extrasynaptic GABAARs expressed by PYRs. Consistently, at spike threshold TGOT induced in most PYRs a significant membrane hyperpolarization and a decrease in firing rate. The source of increased inhibition onto PYRs was represented by stuttering fast-spiking GABAergic interneurons (IN) that directly respond to TGOT with a depolarization and an increase in their firing rate. One putative ionic mechanism underlying this effect could be represented by OtR-induced up-modulation of L-type Ca2+ channels. In conclusion, our results indicate that oxytocin can influence the activity of a subclass of hippocampal GABAergic interneurons and therefore regulate the operational modes of the downstream PYRs by increasing phasic and tonic GABAergic transmission in CA1 region of mouse hippocampus.